Enhancing psychological wellbeing in hip surgery patients through psychological interventions: a scoping review - Lindsay Sullivan; Ellie Ritter; Emily Williams; James P. Moley; Tyler Barker; Sonal Singh; Jennifer Carter; Jay Patel; Marcia Edwards; William K. Vasileff (BMC Musculoskeletal Disorders)
Abstract Background Literature indicates that poor psychological wellbeing can have a negative impact on outcomes following hip surgery. However, limited information is available on psychological interventions for adults with a planned hip surgery. This study describes and synthesizes existing interventions to improve psychological wellbeing in hip surgery patients. Methods We conducted a search of articles using seven electronic databases: CINAHL, Cochrane Library, Embase, PubMed, PsycINFO, SPORTDiscus, and Web of Science. We included all original studies (n = 12) investigating psychological interventions for adults with a planned hip surgery or recovering from hip surgery. Results Most articles focused on adults aged > 60 and individuals recovering from total hip arthroplasty (n = 7). The interventions varied in approach, dose, delivery methods, and timing. The most used approach was self-efficacy enhancing interventions (n = 5) followed by patient education (n = 2) and motivation-based interventions (n = 2). Most interventions (n = 9) were delivered post-operatively either in-person or through a combination of in-person and telephone delivery. Two-thirds of the articles (n = 8) evaluated the effectiveness of the intervention in a randomized controlled trial, with studies varying in sample size and outcome measures. In general, results indicated that psychological interventions positively influenced patient-reported outcomes, including functional status and health-related quality of life, following hip surgery. Conclusion Psychological interventions were generally found to be helpful in improving psychological wellbeing and patient-reported outcomes, such as functional status and health-related quality of life, following hip surgery. Several gaps in the literature were identified, highlighting the need for further research to strengthen the evidence base for psychological interventions in this population.